Reiter’s Syndrome and Crohn’s Disease Coexistence - Sujit Das; Neelima Mehrotra; Ankita Sivastava (Delhi Journal of Ophthalmology)
Reiter’s syndrome is characterized by a classic triad of arthritis, urethritis, and conjunctivitis. Reactive arthritis is a rheumatoid factor-seronegative, human leukocyte antigen B27-linked arthritis. It most commonly strikes individuals aged 20–40 years of age and is more common in men than in women. This inflammatory arthritis manifests several days to weeks after a gastrointestinal or genitourinary infection and is thought to be caused by an autoimmune response involving cross-reactivity of bacterial antigens with joint tissues. Herein, we present a case of Reiter’s syndrome with Crohn’s disease with anterior uveitis in a 22-year-old male patient.